Aplikasi FMA (Fungi Mikoriza Arbuskula) dan Pupuk Kompos Dengan Level Berbeda pada Pertumbuhan dan Produksi Biomasa Rumput Setaria Sphacelata - Oktovianus R. Nahak; Beatrix R. Ulu; Eduardus Y. Neonbeni (JAS, 2022)
An experiment was carried out using FMA and compost fertilizer, to increase the growth and yield of Setaria Sphacelata grass. This study aims to determine the interaction between the combination of FMA (arbuscular mycorrhizal fungi) and compost fertilizer on the growth and production of Setaria Sphacelata grass biomass. The study was conducted in the experimental garden of the Faculty of Agriculture, University of Timor, Kelurahan Sasi, Kota Kefamenanu District, Timor Tengah Utara Regency. The study lasted for 3 months where data collection was carried out in 2 production periods, namely: production I: 45 days after planting and production II 90 days after planting, the study commenced from the beginning of June to the end of August 2019, using a Randomized Group Design (RBD). The first factor is the level of Fungi Micoriza Arbuscula (FMA) (F), namely: Without Fungi Micoriza Arbuscula (control) (F0) and Fungi Micoriza Arbuscula 50 g / planting hole (F1). The second factor is the level of compost (P), namely: Without compost (control) (P0), compost 500 g / planting hole (P1), and compost 750 g / planting hole (P2). Results of variance (ANOVA) showed that the level of FMA and level of compost fertilizer generally did not interact positively (P> 0.05), in influencing all observed variables. The results showed that giving FMA level 50 g / planting hole and compost fertilizer level 500 g / planting hole showed the best results that could be expressed in the highest number of tillers in the first and second production, the heaviest weight of fresh and dry canopy in the first and second production. The conclusions from the results of this research are the number of tillers I = 8.48 and production II = 15.36, fresh weight of production canopy I = 40.97 and production II = 76.77, dry weight production canopy I = 9.50, and production II = 14.32. There was a real difference between treatments with different FMA levels and compost levels on all observed parameters.